Atomic Force Microscopy as a Tool to Explore Triboelectrostatic Phenomena in Mineral Processing. Issue 6 (9th May 2014) - Mirkowska, Monika; Kratzer, Markus; Teichert, Christian; Flachberger, Helmut; Peuker, Urs
Abstract Electrification of insulators has been applied for years in the triboelectrostatic separation of minerals. However, the knowledge of the charge exchange during particle contact is still limited. Here, the electric charging of calcite single crystals upon contact with atomic force microscopy (AFM) probes was studied through different contact types. A combination of contact‐mode AFM and Kelvin probe force microscopy was employed to verify the local surface potentials before and after charging, and focused on the influence of contact time, load force, and applied bias on the charge transfer.